Association between antibiotics and asthma risk among adults aged over 40 years: a nationally representative retrospective cohort study - Sang Min Park; Jooyoung Chang; Sung Min Kim; Jiwon Choi; Sun Jae Park; Young Jun Park; Jaeyi Hong; Seogsong Jeong; Jihun Song; Yoosun Cho (BMJ Open Respiratory Research)
Introduction Several studies have reported that exposure to antibiotics can lead to asthma during early childhood. However, the association between antibiotic use and risk of asthma in the adult population remains unclear. This study aimed to investigate the association between antibiotic use and asthma in adults.Methods We used data from the National Health Insurance Service (NHIS)-Health Screening Cohort, which included participants aged ≥40 years who had health screening examination data in 2005–2006. A total of 248 961 participants with a mean age of 55.43 years were enrolled in this retrospective cohort study. To evaluate antibiotic exposure from the NHIS database for 5 years (2002–2006), cumulative usage and multiclass prescriptions were identified, respectively. During the follow-up period (2007–2019), 42 452 patients were diagnosed with asthma. A multivariate Cox proportional hazard regression model was used to assess the association between antibiotic use and newly diagnosed asthma.Results Participants with antibiotic use for ≥91 days showed a higher risk of asthma (adjusted HR (aHR) 1.84, 95% CI 1.72 to 1.96) compared with participants who did not use antibiotics (n=38 450), with a duration-dependent association (ptrend<0.001). Furthermore, ≥4 antibiotic class user group had an increased risk of asthma (aHR 1.44, 95% CI 1.39 to 1.49) compared with one class of antibiotic use (n=64 698). Also, one class of antibiotic use had a higher risk of asthma (aHR 1.21, 95% CI 1.17 to 1.26) compared with non-users, and it also showed a duration-dependent relationship in all classes, including 1, 2, 3 and ≥4 class group (ptrend<0.001). The duration-response relationship between antibiotic use and increased risk of asthma remained in our sensitivity analyses with the washout and shifting of the index date.Conclusions The duration-response pattern observed in antibiotic use and asthma may suggest the implication of proper antibiotic use and management in adults.